Phenomenon repercussions Globalization on pedagogical action and Educational in Arab society (Journal Of Educational and Psychological Researches, 2014)
Globalization as phenomena has affected   all aspects of life and reflected its impacts to the Arab world politically, economically, and culturally and became a vital field that related directly to our life. This field of searching needs as many studies and Academics as for employing the means that needed to face a national challenge which targeting the Arabic man Character in its ethics and values. This very important thing needs a very important reaction to face that challenge to protect the cultural ARABIC & ISLAMIC characteristics and to take care of education in all its levels and   forms as it is an invincible fort. For that, this field has become as the priority of the studying and researches if the educational institutions. This study has also aimed to make philosophic show that talking about globalization and its reflects on the Arabic society .It also gives a vision of the future of education in Arab homeland. It has reached many results. That globalization and unprecedented began affecting the social and cultural life make changes in the behavior of our young people, which will result phenomenon may be subject to the ebb and natural death, but the effects and implications will remain raised for a long time, particularly those related to communications and satellite TV because it has become part of the system in our daily lives The phenomenon is not, as some believe